Instability in Casson nanofluids for Darcy-Brinkman model. Issue 1 (1st February 2022) - Devi, M; Sharma, J; Gupta, U
Abstract: The convective instability of Casson nanofluids saturating porous medium is investigated analytically and numerically. Darcy-Brinkman law is utilized to frame the momentum equation for the system. The governing equations are simplified using normal mode analysis and linear stability theory. The present study finds the expressions of thermal Rayleigh number for various boundaries and discusses the convective instability under various effects with the help of Wolfram Mathematica software. Out of all the boundaries, the instability of the layer is found to be least for both rigid boundaries. It is established that the convection in the fluid gets delayed due to porosity effects while non-Newtonian property and nano scale effects contribute significantly in making the layer unstable.